The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5402/2012/945162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transoral Robotic Surgery in the Management of Oropharyngeal Cancer: A Review of the Literature

Abstract: Background. Transoral robotic surgery (TORS) is an emerging treatment option for the treatment of head and neck malignancies, particularly for oropharyngeal squamous cell carcinoma (OPSCC). Preliminary studies have demonstrated excellent oncologic and functional outcomes that have led to a resurgence of interest in the primary surgical management of OPSCC. The aim of the present study was to review the evidence base supporting the use of TORS in OPSCC. Methods. Studies evaluating the application of TORS in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 62 publications
2
90
0
3
Order By: Relevance
“…Previous studies have reported a setup time of 15 to 19 minutes, with an operative time of 39 to 84 minutes, depending on the exact procedure and experience level of the team. 12,54 Complications include hemorrhage (2.4%), fistula formation (2.5%), wound infection (2.3%), and pneumonia (0%-7%). 12,15,55 Only a few patients require the long-term use of PEG tubes (0%-9%) or tracheotomies (3%), and the remainder are decannulated within a few days of surgery.…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a setup time of 15 to 19 minutes, with an operative time of 39 to 84 minutes, depending on the exact procedure and experience level of the team. 12,54 Complications include hemorrhage (2.4%), fistula formation (2.5%), wound infection (2.3%), and pneumonia (0%-7%). 12,15,55 Only a few patients require the long-term use of PEG tubes (0%-9%) or tracheotomies (3%), and the remainder are decannulated within a few days of surgery.…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%
“…In cases of OPSCCA, 1-year overall survival rates are reported at higher than 90%, and 2-year survival rates are reported at 80% to 90%, with locoregional recurrence rates of 3% to 6%, following TORS surgery, and the surgery has low complication rates in experienced surgeons. 12,13,15,47,[54][55][56] A recent study by Kaczmar et al 57 highlights that HPV-positive oropharyngeal carcinomas very rarely have locoregional recurrence, and the authors could not find any predictive model using the common prognostic factors. Human papillomavirus status has a significant effect on prognosis, because 2-year overall and disease-free survival rates may rates be up to 20% better in the HPV-positive tumor patient.…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%
“…eHNS is performed with carbon dioxide laser microsurgery or robotic surgical system and has been associated with a resurgence of primary surgical treatment for T1-T2 OPC [16]. Early reports have demonstrated that eHNS is associated with a lower complication rate and faster post-operative recovery [17,18]. Moreover, oncologic outcomes from eHNS appear to be promising.…”
Section: Oropharynx Carcinoma Surgerymentioning
confidence: 99%
“…Moreover, oncologic outcomes from eHNS appear to be promising. A 2012 meta-analysis of over 500 OPSCC patients from 17 retrospective eHNS studies showed 1-year OS of over 90% and 2-year survival between 80 and 90% [18]. Most patients in this meta-analysis with standard indications for adjuvant treatment received adjuvant radiation or chemoradiation.…”
Section: Oropharynx Carcinoma Surgerymentioning
confidence: 99%
“…Many studies have reported the feasibility of transoral robotic surgery (TORS) for the treatment of laryngeal, hypopharyngeal, and supraglottic cancer with excellent results in terms of oncologic radicality and functional preservation [2,3]. Therefore, recently, transoral robotic surgery has been gaining popularity as a new treatment modality for laryngopharyngeal cancer, and it is being performed widely [4].…”
Section: Introductionmentioning
confidence: 99%